Drying of porous media: An algorithm to determine effective parameters - Hong Thai Vu; Trung Dung Nguyen (Vietnam Journal of Science, Technology and Engineering, 2022)
The drying process plays an important role in various industries such as chemical engineering, food, agriculture, and construction. The drying process is a complex one due to the phenomena of heat and mass transfer, which take place simultaneously. In principle, these transport processes can be modelling using continuous and discrete approaches. Following the continuous approach, porous media was simulated as continuous, and effective parameters for heat and mass transfer were employed. In this continuous model, the effective diffusivity and effective thermal conductivity parameters had strong effects on the results. The purpose of this research was to develop an algorithm to determine the effective parameters of the drying of porous media by using a continuous model.